The Relationship Between Attribution of an Act to a State in International Law and Extraterritorial Jurisdiction within the Context of the European Convention on Human Rights - Miray Azaklı Köse (Public and Private International Law Bulletin)
Attribution of an internationally wrongful act to the state is a condition of holding a state responsible in international law and it operates according to special rules for that purpose. In most cases, it is an implied process in the jurisprudence of the European Court of Human Rights. Rules regarding attribution are not only in place while connecting a wrongful act to the State but are also applied when the respondent State’s extraterritorial jurisdiction is in question. In those cases, jurisdiction and attribution, two theoretically distinct issues, become intertwined. This study examines whether that approach is in conformity with international law. Jaloud v Netherlands is a significant judgment since the theoretic distinction between jurisdiction and attribution has been adopted by the European Court of Human Rights. It has been argued that a jurisdiction-establishing act and violation-establishing act must be held separately and that the two might not refer to the same acts in every case. Therefore, the distinction between the two is significant. Another question this study aims to answer is whether the Court applies its own criteria other than “effective control” which is recognized in general international law. To this end, the first part of the study examines what attribution means in international law, and the second part analyzes the Court’s jurisprudence in light of the questions mentioned above.